CHiCAGO: robust detection of DNA looping interactions in Capture Hi-C data. Issue 1 (December 2016) - Cairns, Jonathan; Freire-Pritchett, Paula; Wingett, Steven; Várnai, Csilla; Dimond, Andrew; Plagnol, Vincent; Zerbino, Daniel; Schoenfelder, Stefan; Javierre, Biola-Maria; Osborne, Cameron; Fraser, Peter; Spivakov, Mikhail
Abstract Capture Hi-C (CHi-C) is a method for profiling chromosomal interactions involving targeted regions of interest, such as gene promoters, globally and at high resolution. Signal detection in CHi-C data involves a number of statistical challenges that are not observed when using other Hi-C-like techniques. We present a background model and algorithms for normalisation and multiple testing that are specifically adapted to CHi-C experiments. We implement these procedures in CHiCAGO (http://regulatorygenomicsgroup.org/chicago ), an open-source package for robust interaction detection in CHi-C. We validate CHiCAGO by showing that promoter-interacting regions detected with this method are enriched for regulatory features and disease-associated SNPs.